Development of board game respiratory smart card (restard) in human respiratory system material - Andearsa, Ardias Mema Elza Pasalu; Yuhanna, Wachidatul Linda; Ardhi, Muh. Waskito; Hidayati, Nuril (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2024)
The learning outcomes of Biology subjects in the Kurikulum Merdeka lead to mastery of competencies, materials, and process skills. Biological material is more abstract, teachers must be creative when using teaching media to visualize concretely. Learning media developed by researchers is board games with the name RESTARD (Respiratory Smart Card). The objectives of this study is to find out the form of development of the Board Game Respiratory Smart Card (RESTARD) in Human Respiratory System Material that is valid and feasible for biology learning. The method of the research is a Research and Development (R&D) using 4-D instructional design. The population for the practicality test was all class XI of SMAN 6 Madiun, totaling 360 students. The sample for this research was class XB with a total of 72 students. Data collection techniques were carried out using interviews, filling out validation sheets from material and teaching media experts, and filling out practicality questionnaires by students. The result of this research is that the development of the RESTARD board game on respiratory disorders has been successfully carried out. RESTARD consists of 6 main types of cards, namely organ cards, O2 cards, CO2 cards, sneezing cards, breathing cards, and sick/health cards. The validation results from media experts stated that the RESTARD card media received an average score of 93 with the criteria very valid for use. The results of the material expert validation stated that the RESTARD card media received an average score of 91 with criteria very valid for use. The practicality in small class showed that 91 score with very practicality. Result in large class show that the average of score is 94, with very practicality. The conclusion is RESTARD media is declared valid, practical and can be used to support learning of respiratory system material.